A Bcl-2 Associated Athanogene (bagA) Modulates Sexual Development and Secondary Metabolism in the Filamentous Fungus Aspergillus nidulans - Jain, Sachin; Wiemann, Philipp; Thill, Elizabeth; Williams, Brett; Keller, Nancy P.; Kabbage, Mehdi (Frontiers in Microbiology, 2018)
The Bcl-2 associated athanogene (Bag) family is a multifunctional group of proteins distinguished by a conserved region known as the Bag domain (BD). Herein, we discuss the discovery and characterization of a Bag protein in the model genetic fungus Aspergillus nidulans, we designated BagA. BagA shares striking similarities in 3D structure, domain organization, amino acid properties, and Hsp70 binding surfaces to animal and plant Bags. While Hsp70 binding is a common feature of Bag proteins, our experimental evidence shows that BagA does not cooperate with A. nidulans Hsp70s, suggesting this association may not be a universal feature of Bag proteins. Gene expression of bagA was strongly induced during sexual development suggesting a role in developmental processes. Accordingly, the deletion of bagA (∆bagA) negatively impacted sexual development, while its overexpression resulted in constitutive induction of sexual fruiting bodies and spores. Asexual and sexual development was linked to secondary metabolism in A. nidulans. Our data show that the deletion of bagA also provoked an altered secondary metabolite (SM) profile in both sexual and vegetative growth phases. Indeed, LC-MS analysis showed a significant enrichment of SMs in ∆bagA, including novel metabolites not produced by wild type strain. Enrichment of SMs in ∆bagA strain is particularly intriguing, and suggest that altering cellular homeostasis can be used as a provocative strategy to activate cryptic metabolites and uncover novel bioactive compounds. Overall, our results indicate that Bag proteins in filamentous fungi share developmental regulatory roles with their animal and plant counterparts. We also show a potentially unique role for BagA in modulating secondary metabolism in A. nidulans. To our knowledge, this study provides a first insight into Bag function in filamentous fungi.